Reversible palm vein authenticator design with quantum dot cellular automata for information security in nanocommunication network - Debnath, Bikash; Das, Jadav Chandra; De, Debashis; Ghaemi, Ferial; Ahmadian, Ali; Senu, Norazak (Institute of Electrical and Electronics Engineers Inc., 2020)
Palm vein pattern recognition is one of the most promising and rapidly developing fields of study in biometrics, which makes it an important solution for identity security in biometrics-based user identification systems. Quantum-dot Cellular Automata (QCA) is a developing field of nanotechnology which facilitates the creation of nano-scale logical circuits. Irreversible technology has faced some difficulties, such as higher heat energy dissipation. Reversible logic is therefore essential where heat dissipation is almost insignificant. This article proposes QCA design of a reversible circuit for palm vein authentication utilizing the Feynman gate. Fully reversible Feynman gate is designed. Using this newly designed Feynman gate the palm vein authenticator circuit is designed. The theoretical values and the results of the simulation correspond to the reliability of the planned circuit. Circuit complexity and circuit cost are explored. Validation of authenticated users by the proposed authenticator explores its design accuracy as per theoretical values. Energy dissipation of the proposed designs shows that it remains within Lauderer's limit (0.06meV). This proves that the circuits designed are fully reversible in nature and dissipates very less amount of energy. Comparison with recent QCA state of the art architectures explores its